XBRL, semantic web and web services. (1st January 2011) - Qin, Li
Computer and information technology innovations have revolutionised how business is conducted and how information is exchanged across systems. Technologies, such as eXtensible Business Reporting Language (XBRL), semantic web and web services, have emerged to transform the landscape of business information provision, exchange and consumption. The focus of this paper is to investigate the connections among these technologies, and to further discuss their joint impact upon the business information interchange. Specifically, this paper presents bridging XBRL to semantic web and semantic web services as future technological trends, which will affect business information automation, currency, availability, transparency, accuracy, relevancy, system flexibility and adaptability, and the corporate communication model.